Decolonizing Post-Truths in Mediatic Encounters for Farha (2021) and Half Widow (2017) - Aamir, Rabia (Journal of Research in Humanities, 2024)
While Zionism may argue for the purity of Hebrew Labor “Avodah ‘Ivrit” in the context of Palestine, and Kashmir The Story (2019) may be staging a narrative in the context of Kashmir, the historical facts about Palestine and Kashmir state a different perspective. Therefore, some critics have sought the implications of films like Exodus (1960) and programs like Bharat Ek Khoj (1988) playing a pivotal role in shaping our recent history. Subverting some dominant tropes depicted in such media depictions and engaging with McIntyre’s book post-Truth (2018), Alterman’s discussions in his works, What Liberal Media? (2003) and We are not One (2023), and Santos’ theorizing about decolonizing history, this paper studies two contemporary filmic depictions of Farha (2021) and Half Widow (2017). In this age of increasing implonialism, a phenomenon comprising the elements of colonialism, imperialism, fascism, and despotism, the paper discusses some decolonial options to read the politics of mediatic supremacist standards set to prioritize some mediatic depictions over others.